2019
DOI: 10.1039/c8ra10282a
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of selenium-containing amphiphilic aliphatic polycarbonate as an oxidation-responsive drug delivery vehicle

Abstract: Although functional aliphatic polycarbonates (APCs) have attracted prominent research interest as stimuli-responsive biomaterials, the majority of functional APCs are fabricated by detrimental organometallic catalysts or organo-catalysts. Herein, a facile synthetic strategy based on enzymatic polymerization was developed to construct a selenium-containing amphiphilic aliphatic polycarbonate (mPEG-b-CMP 45 ). Specifically, the selenium in its backbone framework underwent a hydrophobichydrophilic transition upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Moreover, CLSM studies revealed an internalization efficiency and drug release inside the cancer cells. Yang et al [136] developed ROS-responsive nanocarriers based on selenium-containing amphiphilic APC. The DOX-loaded nanoparticles were rapidly disrupted under biologically relevant concentrations of H 2 O 2 , thus releasing the encapsulated drug for inducing cancer cells apoptosis.…”
Section: Ros-responsive Apc Nanocarriersmentioning
confidence: 99%
“…Moreover, CLSM studies revealed an internalization efficiency and drug release inside the cancer cells. Yang et al [136] developed ROS-responsive nanocarriers based on selenium-containing amphiphilic APC. The DOX-loaded nanoparticles were rapidly disrupted under biologically relevant concentrations of H 2 O 2 , thus releasing the encapsulated drug for inducing cancer cells apoptosis.…”
Section: Ros-responsive Apc Nanocarriersmentioning
confidence: 99%
“…Examples of molecular entities incorporated into these polymers and responsible for stimuli‐responsive characteristics are summarized in Figure . Due to technological importance of particular interest are responses to pH, [ 1–5 ] temperature, [ 6–14 ] H 2 O, [ 15–21 ] redox agents, [ 22–28 ] CO 2 , [ 29–34 ] glucose, [ 35 ] enzyme, [ 36–38 ] electric [ 39 ] and/or magnetic field, [ 40–42 ] electromagnetic radiation, [ 43,44 ] and mechanical forces [ 45–48 ] which are discussed in this review.…”
Section: Introductionmentioning
confidence: 99%
“…A) Schematic illustration of synthesis of a series of ssPESs by polycondensation of SS‐diacid with various diols and their reductive degradation under reducing conditions (Adapted with permission [ 186 ] Copyright 2012, Wiley‐VCH GmbH); B) Chemical structure of MPEG‐P(BHD‐SS)‐MPEG, the formation of micelles by self‐assembly, and schematic illustration of the GSH‐induced drug release associated by self‐decomposition of the micellar carriers (Adapted with permission [ 187 ] Copyright 2015, American Chemical Society); C) Chemical structure of polycarbonates with thioketal unit in sidechain, and schematic illustration of ROS induced self‐cleavage (Adapted with permission [ 26 ] Copyright 2019, American Chemical Society); D) ROS‐triggered degradation of the self‐assembled selenide containing polymer nanomaterials based on the selenoxide elimination reaction (Adapted with permission [ 25 ] Copyright 2019, The Royal Society of Chemistry); E) The synthesis of selenide‐based block copolymers and preparation of DOX‐loaded micelles as oxidation responsive drug delivery vehicle (Adapted under the terms of the Creative Commons Attribution 3.0 Unported License. [ 27 ] Copyright 2019, The Royal Society of Chemistry); F) Self‐assembly of thioether‐based block copolymers and their oxidation behavior (Adapted with permission [ 188 ] Copyright 2018, The Royal Society of Chemistry).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic polymerization provides a new path for the synthesis of functionalized polyester materials with lots of advantages, such as high catalytic activity, high selectivity, mild reaction conditions, and the use of green biocatalysts (28)(29)(30)(31)(32). In recent years, especially cheap and readily available lipase has attracted extensive attention in the synthesis of bio-based polyesters, owing to the fact that both monomers and catalysts come from renewable resources (33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%